2011
DOI: 10.1039/c1cc13724g
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun antimony doped tin oxide (ATO) nanofibers as a versatile conducting matrix

Abstract: Nanoparticles of ATO (antimony doped tin oxide) were used to produce thick conductive, free standing mats of nanofibers via electrospinning. These fibrous mats were incorporated into polymer films to produce a transparent conducting polymer foil. Moreover, the fiber mats can serve as porous electrodes for electrodeposition of Prussian Blue and TiO 2 and were tested in dye-sensitized solar cells.TCO (transparent conducting oxide) materials are widely used in opto-electronic applications as transparent electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Ostermann et al . worked on similar material, antimony tin oxide, and because of those difficulties, they concluded that it was impossible to obtain continuous oxide nanofibrous layers of significant thickness by direct deposition on the solid substrate, due to inevitable breaking of fibers and delamination of the layer . For that reason, some of the early reports, as well as all of the later applications of ITO nanofibers have been performed using free‐standing mats ,.…”
Section: Introductionmentioning
confidence: 99%
“…Ostermann et al . worked on similar material, antimony tin oxide, and because of those difficulties, they concluded that it was impossible to obtain continuous oxide nanofibrous layers of significant thickness by direct deposition on the solid substrate, due to inevitable breaking of fibers and delamination of the layer . For that reason, some of the early reports, as well as all of the later applications of ITO nanofibers have been performed using free‐standing mats ,.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure could be optimized for better transparency but at the cost of a higher sheet resistance (Figure ). A lower sheet resistance of 400 Ω sq −1 for ATO was obtained by depositing porous layers in the form of free‐standing mats and using ATO nanoparticles as precursors . Similarly, AZO nanofibers have been prepared and it was found that the grain size becomes lower with rising Al doping levels .…”
Section: Preparation Of Porous Transparent Conductive Oxidesmentioning
confidence: 79%
“…The herein reported TCO NPs possess diameters of 3–6 nm, are colloidally stable, can be produced on a multi‐gram scale and are well‐suited for spin‐coating nanoporous, transparent, and conductive TCO thin films7 (see Scheme ) with potential utility in lithium ion batteries, solar and photo‐electrochemical cells, electrochromics and sensors, flat‐panel displays, transparent thin‐film transistors, optoelectronic devices, and photonic crystal architectures 8–12. Additionally, such TCO dispersions can potentially be ink‐jet printed4, 13 or electrospun into TCO nanofibers 14…”
Section: Methodsmentioning
confidence: 99%